Negative manifestations of internalized extreme filial piety culture among Korean high school student athletes: dropping out, “Athlete Melt”, tie-in sale, and “Running Away” - Yoon, SangJin; Lim, SeaMi (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigates the adverse impact of extreme filial piety culture on the career trajectories of elite Korean amateur athletes following professional league contract failures.MethodsUsing narrative interviews and participant observation, we explored the experiences of high school student-athletes who were unable to transition to professional sports, secure university admission as athletes, or chose to abandon their athletic careers.ResultsOur analysis revealed four key phenomena: some student-athletes drop out of high school or forgo university to pursue other careers; illicit “tie-in sales” allow parents to leverage sports performance for admission to prestigious universities; several student-athletes run away from home due to abusive or unsupportive environments and feelings of entrapment; and internalized extreme filial piety generates overwhelming guilt as athletes feel compelled to repay parental sacrifices through their success.DiscussionThese findings highlight the need for policy interventions and support systems that broaden career options, curb excessive parental and coaching pressures, and foster greater autonomy in student-athletes’ decision-making.